Іронічний Григір Тютюнник (деякі спостереження) - Мороз, Л. (Слово і Час, 2021)
У спадщині Григора Тютюнника та персонажах його творів авторка с постерігає ознаки (окремі та у своєрідному поєднанні) іронічності
в широкій градації — від легкого поблажливого насміху до сарказму,
трагічної іронії, подекуди й трагіфарсу. Ідеться про оповідання «Комета», «Гвинт», «Поминали Маркіяна», «Грамотний», «Сміхо-
та», «Нюра», «Чудасія», «Син приїхав», «Медаль», про повісті
«День мій суботній», «Житіє Артема Безвіконного». One of the most dramatic writers of the 2nd half of the 20th century Hryhir Tiutiunnyk
was remembered by all his contemporaries who worked in the cultural sphere as a person
endowed with a keen sense of humor, rare wit, and unique artistry (in various genres, both
dramatic and comedic). Th is paper is a reflection on how in the works by Hryhir Tiutiunnyk,
killed by the totalitarian system in 1980, the well-known dominants of “love and
pain” are deepened by irony, in all the immensity of its shades and meanings. The writer
did not use any words from the political lexicon but instead unmasked the totalitarian system
by depicting (mostly through apt expressions and details) the behavior and destinies of
people oppressed or destroyed by it. His irony is mild, lenient, or even somewhat sympathetic.
In the stories reviewed in the paper, namely “Screw”, “Niura”, “The Feast in Memory
of Markiian”, “The Son Has Arrived”, the mentioned nuances of the means of irony are used
in rather complex, sometimes weird combinations (“The Literate”, “Laughter”), revealing
the ardent indifference of the author who tried (sometimes successfully) to pretend to be an
outsider — an unworried or even superior narrator. In such works as “The Feast in Memory
of Markiian” and “Medal”, the death itself or its obvious approach causes the appearance of
tragicomic elements. However, in the latter, the tragic irony is not related to the character,
but to the props of the stage action, in which the people resembling mannequins represent
the village and district authorities and pretend to award a starving man as “the best animal
breeder”.
Some of Hryhir Tiutiunnyk’s characters, as in the short story “Oddity” and the story
“My Saturday”, rise to a sarcastic mockery of oppressors: the specificity of the Soviet-communist
officials lies in the fact that they don’t even realize the absurdity of their activities,
which lack any humanistic principles. The literary world of the writer, despite its seeming
simplicity, is extremely complex in terms of inner subtleties of thoughts, emotions, and conflicts.